Aqueous zinc ion electrolyte additive containing maltitol and application thereof
By using maltitol as an electrolyte additive in aqueous zinc ion batteries, chemically adsorbs it on the surface of the zinc electrode to form a protective film, solving the problem of zinc negative electrode corrosion and dendrite, and significantly improving the cycle life and electrochemical stability of the battery.
Patent Information
- Application Number
- CN202311229646.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-09-22
AI Technical Summary
The zinc negative electrode in aqueous zinc ion batteries is prone to react with the aqueous electrolyte, resulting in accelerated hydrogen evolution reaction, increased corrosion rate and irreversible by-product generation, thereby reducing battery capacity and Coulomb efficiency.
Maltitol is used as an additive for aqueous zinc ion electrolyte, and adheres to the surface of zinc metal anode through chemical adsorption, preventing direct contact between water and zinc electrodes, forming a protective film, thereby inhibiting the growth and corrosion reaction of zinc dendrites.
Effectively inhibit the electrochemical side reaction of zinc negative electrode and solid-liquid interface reaction, extend the cycle life of the battery, improve the electrochemical stability performance, and significantly improve the stable cycle times of zinc ion batteries.
Smart Images

Figure CN117080584B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous batteries, and in particular relates to an aqueous zinc ion electrolyte additive containing maltitol and application thereof. Background Art
[0002] Aqueous zinc-ion batteries (ZIBs) are considered to be very promising energy storage systems due to their good safety, low cost and environmental friendliness, and have been widely studied. Although rapid progress has been made in the research of high-performance cathode materials, there are still deficiencies in the research on zinc anodes. For example, zinc anodes with high thermodynamic activity are very easy to react with aqueous electrolytes, undergoing hydrogen evolution reactions, accelerating the corrosion rate and forming irreversible byproducts. In most alkaline electrolytes, since zinc has a lower redox potential than hydrogen, zinc can spontaneously form corrosion micro-batteries that produce severe dendrites and non-conductive passivation byproducts, such as Zn(OH)2, resulting in battery capacity decay and reduced Coulombic efficiency.
[0003] In order to solve the inherent shortcomings of zinc negative electrodes, technicians in this field have proposed many strategies to improve the performance and protection of zinc negative electrodes. At present, the methods for solving the corrosion and dendrite problems of aqueous zinc ion batteries are mainly divided into two categories: zinc negative electrode modification and electrolyte optimization. Among them, electrolyte optimization is a simple, effective and easy-to-implement method to inhibit the formation and growth of dendrites. Currently, the commonly used electrolyte additives are mainly organic polymer electrolyte additives, which can be selectively adsorbed on the zinc deposition site, inducing uniform distribution of ion concentration and electric field near the zinc negative electrode, thereby improving the interface environment between the zinc negative electrode and the electrolyte, and avoiding excessive growth of zinc dendrites, but there is a defect of poor cycle stability. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes an aqueous zinc ion electrolyte additive containing maltitol and its application, the electrolyte additive can be attached to the surface of the zinc metal anode by chemical adsorption, so that the zinc deposition is more uniform and slow, and the larger nucleation overpotential can promote the formation of a finer grain zinc deposition layer, and also lead to the reduction of nucleation sites and nucleation speed, thereby inhibiting the growth of zinc dendrites, and finally improving the electrochemical stability and cycle life of the aqueous zinc ion battery. The present invention has the characteristics of simple process, low cost, green and environmental protection, which is of great significance to promoting the improvement of the cycle life of the aqueous zinc ion battery and commercialization.
[0005] To achieve the above object, the present invention provides an aqueous zinc ion electrolyte additive containing maltitol, wherein the additive in the aqueous zinc ion electrolyte is maltitol.
[0006] The mechanism of action of xylitol and maltitol is different. Xylitol molecules reconstruct the hydrogen bond network of the electrolyte through hydrogen bonds and expel active water molecules to regulate the transmission and deposition of zinc ions. After adding maltitol to the aqueous zinc ion electrolyte, maltitol is adsorbed on the surface of the zinc electrode through chemical action, which hinders the direct contact between the water in the electrolyte and the zinc electrode, forming a protective film, thereby inhibiting the side reactions related to the zinc electrode and water, and further slowing down the growth of zinc dendrites. Compared with xylitol, a commonly used additive in the prior art, maltitol also has great advantages in performance. Batteries with maltitol added can stably cycle for more than 2,000 hours, while batteries with xylitol added can only stably cycle for about 1,100 hours.
[0007] Furthermore, the concentration of maltitol in the aqueous zinc ion electrolyte is 0.01 mol / L to 0.1 mol / L (ie, 10 mM to 100 mM).
[0008] The invention discloses an application of the aqueous zinc ion electrolyte additive containing maltitol in an aqueous zinc ion battery or a zinc ion electrochemical energy storage device.
[0009] The invention discloses an aqueous zinc ion electrolyte, wherein the aqueous zinc ion battery electrolyte consists of a solvent, an electrolyte and an aqueous zinc ion electrolyte additive containing maltitol.
[0010] Furthermore, in the aqueous zinc ion electrolyte, the solvent is deionized water; and the electrolyte is zinc sulfate heptahydrate and / or manganese sulfate monohydrate.
[0011] Furthermore, the concentration of zinc sulfate heptahydrate in the aqueous zinc ion battery electrolyte is 1 mol / L to 3 mol / L.
[0012] Furthermore, the concentration of manganese sulfate monohydrate in the aqueous zinc ion battery electrolyte is 0.01 mol / L to 0.3 mol / L, and manganese sulfate monohydrate supplements the Mn consumed during the operation of the full battery. 2+ .
[0013] The aqueous zinc ion battery electrolyte is used in an aqueous zinc ion battery or a zinc ion electrochemical energy storage device.
[0014] An aqueous zinc ion battery consists of a positive electrode, a negative electrode, a diaphragm and the aqueous zinc ion electrolyte.
[0015] Furthermore, in the aqueous zinc ion battery, the positive electrode active material is MnO2, the negative electrode material is zinc foil, and the diaphragm material is glass fiber.
[0016] Furthermore, the positive electrode active material MnO2 is prepared by a hydrothermal synthesis method: first, 5 mmol K2MnO4 is dissolved in 70 mL H2O and stirred clockwise with a glass rod. After it is dissolved, 1.75 mL of concentrated HCl (concentration is 12 mol / L) is added. After stirring at room temperature (25±2°C) for 30 min, they are transferred to a 200 mL reactor respectively, and then the reactor is placed in a drying oven at 100°C and heated for 6 h to obtain the positive electrode active material MnO2.
[0017] Furthermore, when the positive electrode active material is MnO2, the preparation method of the positive electrode is as follows: first, MnO2 and a conductive agent (Ketjen black) are ground separately with a mortar, and then MnO2, a conductive agent (Ketjen black) and a binder (PVDF) are mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone is used as a solvent. After grinding evenly in a mortar to obtain a slurry, a 200μm scraper is used on a coating infrared dryer to evenly apply the ground slurry on a PE (polyethylene) film, and then the slurry is placed in a vacuum drying oven to dry. After drying, a cutting machine is used to cut it into a positive electrode sheet with a diameter of 12mm, which is the positive electrode.
[0018] Compared with the prior art, the present invention has the following advantages and technical effects:
[0019] The present invention uses maltitol as an additive for an aqueous zinc ion battery electrolyte, preferably using 1.8M ZnSO4 as a basic electrolyte. During zinc deposition, maltitol molecules can be preferentially attached to the surface of a zinc metal anode through chemical adsorption, reducing the direct contact between free water and the zinc metal surface, thereby reducing the hydrogen evolution reaction between free water and the zinc metal surface, and inhibiting the generation of byproduct sulfate. In addition, a zinc ion battery containing maltitol can generate a larger nucleation overpotential, which can promote the formation of a finer grain zinc deposition layer and also lead to a reduction in nucleation sites and nucleation speed, thereby inhibiting the growth of zinc dendrites, which helps uniform deposition of zinc ions on the surface of the zinc metal anode.
[0020] In summary, the present invention uses maltitol as an electrolyte additive to effectively inhibit electrochemical side reactions and uncontrollable solid-liquid interface reactions on the surface of the zinc negative electrode, thereby alleviating zinc corrosion and zinc negative electrode passivation problems. Maltitol is widely available, inexpensive, green and environmentally friendly, and can be produced on a large scale, which is of great significance for building high-performance, safe, environmentally friendly and low-cost aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0022] Figure 1 The contact angle test diagrams of the electrolytes used in Example 1(a) and Comparative Example 1(b) are shown.
[0023] Figure 2 These are SEM morphology images of the zinc electrodes in Example 1 and Comparative Example 1 after 50 cycles of deposition in the electrolyte, wherein (a) and (c) are Example 1, (b) and (d) are Comparative Example 1, (a) and (b) are SEM morphology images magnified 200 and 2000 times, respectively, and (c) and (d) are SEM morphology images magnified 200 and 2000 times, respectively.
[0024] Figure 3 It is a rate performance diagram of the Zn / / Zn symmetric battery of Example 1 (1.8M ZnSO4+30mM maltiol) and Comparative Example 1 (1.8M ZnSO4).
[0025] Figure 4 It is a cycle performance diagram of the Zn / / Zn symmetric battery of Example 1 (1.8M ZnSO4+30mM maltiol) and Comparative Example 1 (1.8M ZnSO4).
[0026] Figure 5 Tafel curves of the aqueous zinc ion three-electrode battery assembled by Example 2 (1.8M ZnSO4+30mM maltiol) and Comparative Example 2 (1.8M ZnSO4).
[0027] Figure 6 This is a rate performance diagram of the aqueous zinc ion battery Zn / / MnO2 assembled from Example 3 (1.8M ZnSO4+30mM maltiol) and Comparative Example 3 (1.8M ZnSO4).
[0028] Figure 7 It is a long cycle performance diagram of the aqueous zinc ion battery Zn / / MnO2 assembled in Example 3 (1.8M ZnSO4+30mM maltiol) and Comparative Example 3 (1.8M ZnSO4), wherein ZnSO4-CE is the coulombic efficiency of the aqueous zinc ion battery Zn / / MnO2 assembled in Comparative Example 3 (1.8M ZnSO4), and ZnSO4+30mM maltiol-CE is the coulombic efficiency of the aqueous zinc ion battery Zn / / MnO2 assembled in Example 3 (1.8M ZnSO4+30mMmaltiol). DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] Unless otherwise specified, the room temperature in the embodiments of the present invention refers to 25±2°C.
[0035] Example 1
[0036] (1) Take 2.588 g of zinc sulfate and disperse it in deionized water, and then make a 5 mL solution. Then, stir it magnetically at room temperature until the zinc sulfate is completely dissolved. Then, let it stand to obtain a 1.8 M ZnSO4 electrolyte.
[0037] (2) Take 5 mL of the above ZnSO4 electrolyte, add 0.0516 g of maltitol thereto, stir it magnetically at room temperature until the maltitol is completely dissolved, and then let it stand to obtain an aqueous zinc ion electrolyte containing 30 mM maltitol.
[0038] Example 2
[0039] Disperse 25.88g zinc sulfate and 0.2582g maltitol in deionized water and prepare 25mL solution, then stir it magnetically at room temperature until zinc sulfate and maltitol are completely dissolved to obtain an aqueous zinc ion electrolyte containing 30mM maltitol, and then transfer the electrolyte to a 25mL three-electrode reaction cell. Cut two 1cm 2 *1cm 2 The zinc sheet was used as the working electrode and reference electrode, and AgCl was used as the reference electrode to form a three-electrode system. The Tafel test was carried out on the three-electrode system using Chenhua electrochemical workstation.
[0040] Example 3
[0041] The only difference between this embodiment and embodiment 1 is that 0.1 M MnSO4 is added to the electrolyte.
[0042] Example 4
[0043] (1) Take 4.313 g of zinc sulfate and disperse it in deionized water, and then make a 5 mL solution by fixed volume. Then, stir it magnetically at room temperature until the zinc sulfate is completely dissolved, and then let it stand to obtain a 3 M ZnSO4 electrolyte.
[0044] (2) Take 5 mL of the above ZnSO4 electrolyte, add 0.086 g of maltitol thereto, stir it magnetically at room temperature until the maltitol is completely dissolved, and then let it stand to obtain an aqueous zinc ion electrolyte containing 10 mM maltitol.
[0045] Example 5
[0046] (1) 1.438 g of zinc sulfate was dispersed in deionized water and the solution was fixed to 5 mL. The solution was then magnetically stirred at room temperature until the zinc sulfate was completely dissolved. The solution was then allowed to stand to obtain a 1 M ZnSO4 electrolyte.
[0047] (2) Take 5 mL of the above ZnSO4 electrolyte, add 0.43 g of maltitol thereto, stir it magnetically at room temperature until the maltitol is completely dissolved, and then let it stand to obtain an aqueous zinc ion electrolyte containing 50 mM maltitol.
[0048] Example 6
[0049] The preparation process of ZnSO4 electrolyte is the same as that of Example 1. Take 5 mL of the above ZnSO4 electrolyte, add 0.86 g of maltitol thereto, stir it magnetically at room temperature until the maltitol is completely dissolved, and then let it stand to obtain an aqueous zinc ion electrolyte containing 100 mM maltitol.
[0050] Example 7
[0051] The only difference between this embodiment and embodiment 1 is that 0.01 M MnSO4 is added to the electrolyte.
[0052] Example 8
[0053] The only difference between this embodiment and embodiment 1 is that 0.3 M MnSO4 is added to the electrolyte.
[0054] Comparative Example 1
[0055] Compared with Example 1, the only difference is that maltitol is not added, and a 1.8M ZnSO4 electrolyte without maltitol is prepared.
[0056] Comparative Example 2
[0057] Compared with Example 2, the only difference is that all zinc ion electrolytes in the three-electrode system do not contain maltitol additive.
[0058] Comparative Example 3
[0059] Compared with Example 3, the only difference is that maltitol is not added, and 1.8M ZnSO4 and 0.1M MnSO4 electrolytes without maltitol are prepared.
[0060] The prepared electrolytes were used to assemble Zn / / Zn symmetric cells and Zn / / MnO2 full cells, and charge and discharge tests were performed on a BlueDian battery test system.
[0061] The contact angles of the zinc ion electrolytes prepared in Example 1 and Comparative Example 1 were tested using a contact angle measuring instrument. Figure 1 As shown in (a) and (b), the contact angles are 57° and 96° respectively. The contact angle of the electrolyte with maltitol added on the zinc foil becomes smaller, indicating that the aqueous zinc ion electrolyte containing maltitol has greater adsorption energy on the zinc foil. In the battery, maltitol molecules are more easily adsorbed on the surface of the zinc foil than water molecules, which can hinder the direct contact between water molecules and the zinc metal anode, thereby alleviating the hydrogen evolution corrosion reaction at the interface between the zinc metal anode and the electrolyte.
[0062] Figure 2 The Zn / / Zn symmetric cells of Example 1 and Comparative Example 1 were prepared at a current density of 1 mA / cm 2 , deposition capacity is 1 mAh / cm 2SEM images after 50 cycles under the test conditions of , where (a) and (b) are Zn / / Zn symmetric batteries assembled with the electrolyte of Example 1, and (c) and (d) are Zn / / Zn symmetric batteries assembled with the electrolyte of Comparative Example 1. From (a) and (c), it can be seen that the surface of the zinc anode containing maltitol is smoother than that of the zinc anode without maltitol, and zinc ions are mostly deposited horizontally on the surface of the zinc anode. (c) shows that zinc ions are deposited in a disorderly manner on the surface of the zinc anode. From the further enlarged (b) and (d), it can be seen that cellular byproducts have been generated on the surface of the zinc anode without maltitol.
[0063] Figure 3 The Zn / / Zn symmetric cells of Example 1 and Comparative Example 1 were prepared at a current density of 1 mA / cm 2 , 3mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 , deposition capacity is 1 mAh / cm 2 Rate performance diagram under test conditions. It can be seen that the battery containing maltitol shows a more stable voltage distribution than the battery without maltitol. In addition, when the current density is restored to 10mA / cm 2 When the battery containing maltitol was charged, it could still work normally, but the battery without maltitol had a short circuit, which proved that the maltitol additive could help improve the rate performance of zinc-ion batteries.
[0064] Figure 4 The Zn / / Zn symmetric cells of Example 1 and Comparative Example 1 were prepared at a current density of 1 mA / cm 2 , deposition capacity is 1 mAh / cm 2 The cycle performance diagram under the test conditions of . It can be seen that the cycle life of the battery containing maltitol can reach more than 2500h, and the battery without maltitol has a short circuit at only about 160h, which proves that maltitol additives can significantly improve the cycle life of zinc-ion batteries.
[0065] Figure 5 The Tafel curves of the aqueous zinc ion three-electrode battery measured in Example 2 and Comparative Example 2 show that the corrosion current of the three-electrode battery containing maltitol is 8.750×10 -4 mA / cm 2 , which is much smaller than the corrosion current of the three-electrode battery without maltitol, which is 4.830×10 -3 mA / cm 2 This proves that maltitol additives can slow down the corrosion of aqueous zinc ion electrolyte on battery electrodes. Other sugar alcohol additives such as xylitol mainly regulate the Zn 2+With H2O molecules and SO4 2- ions and enhance ion migration and inhibit HER by directional reconstruction of hydrogen bonds; however, maltitol is chemically adsorbed on the surface of zinc foil, which can hinder the direct contact between water molecules and the zinc metal anode, thereby alleviating the hydrogen evolution corrosion reaction at the interface between the zinc metal anode and the electrolyte. Other types of sugar alcohols cannot achieve this effect.
[0066] Figure 6 The aqueous zinc ion electrolyte prepared in Example 3 and Comparative Example 3 was used to assemble a Zn / / MnO2 full battery. The current density was 0.2A / g, 0.5A / g, 1A / g, 2A / g, 4A / g, and the deposition capacity was 1mAh / cm 2 Rate performance under test conditions. It can be seen that the batteries containing maltitol have higher specific capacity, and can still maintain a stable specific capacity after the current density is restored to 0.2A / g, which has better reversibility than the battery without maltitol, indicating that the addition of maltitol can improve the electrochemical performance of the battery.
[0067] Figure 7 The aqueous zinc ion electrolyte prepared in Example 3 and Comparative Example 3 was used to assemble a Zn / / MnO2 full battery. It can be seen that the capacity of the battery containing maltitol decays more slowly than that of the battery without maltitol, and has higher coulombic efficiency and capacity retention rate.
[0068] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. An aqueous zinc ion electrolyte additive containing maltitol, characterized in that: The additive in the aqueous zinc ion electrolyte is maltitol; The concentration of maltitol in the aqueous zinc ion electrolyte is 0.01 mol / L to 0.1 mol / L; Batteries with an aqueous zinc ion electrolyte additive containing maltitol can cycle stably for more than 2,000 hours.
2. Use of the aqueous zinc ion electrolyte additive containing maltitol according to claim 1 in an aqueous zinc ion battery or a zinc ion electrochemical energy storage device.
3. An aqueous zinc ion electrolyte, characterized in that The aqueous zinc ion battery electrolyte consists of a solvent, an electrolyte and the aqueous zinc ion electrolyte additive containing maltitol according to claim 1.
4. The aqueous zinc ion electrolyte according to claim 3, characterized in that The solvent is deionized water; the electrolyte is zinc sulfate heptahydrate and / or manganese sulfate monohydrate.
5. The aqueous zinc ion electrolyte according to claim 4, characterized in that The concentration of zinc sulfate heptahydrate in the aqueous zinc ion electrolyte is 1 mol / L to 3 mol / L.
6. The aqueous zinc ion electrolyte according to claim 4, characterized in that The concentration of manganese sulfate monohydrate in the aqueous zinc ion electrolyte is 0.01 mol / L to 0.3 mol / L.
7. Use of the aqueous zinc ion electrolyte according to any one of claims 3 to 6 in an aqueous zinc ion battery or a zinc ion electrochemical energy storage device.
8. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery consists of a positive electrode, a negative electrode, a separator and the aqueous zinc ion electrolyte according to any one of claims 3 to 6.
9. The aqueous zinc ion battery according to claim 8, characterized in that: The positive electrode active material is MnO2, the negative electrode material is zinc foil, and the separator material is glass fiber.
Citation Information
Patent Citations
Electrolyte additive, electrolyte, aqueous zinc ion battery containing electrolyte and preparation method of aqueous zinc ion battery
CN116683048A
Cited By
Zinc ion battery electrolyte based on isomaltitol and maltitol as well as preparation method and application of zinc ion battery electrolyte
CN121601811A
Isomalt and maltitol-based zinc-ion battery electrolyte, preparation method and application thereof
CN121601811B